Influence of dynamic loadings from operating of underground railway on the deflected mode of high-rise buildings - Дзюба, А.В.; Миронець, Т.Л. (Proceedings of National Aviation University, 2010)
Influence of motion of train of underground passage on height housing building is considered. Recommendations in relation to protecting of buildings and buildings from a vibration are given. Basic from them: to increase building inflexibility; to apply barriering constructions in the array of soil.